Chemical reactor analysis and design fundamentals - Rawlings, James B. (Nob Hill Publishing, 2002)
Setting the stage - The stoichiometry of reactions - Review of chemical equilibrium - The material balance for chemical reactors - Chemical kinetics - The energy balance for chemical reactors - Fixed-bed catalytic reactors - Mixing in chemical reactors - Parameter estimation for reactor models - Computational methods.